2014
DOI: 10.1016/j.snb.2014.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-nanotube-deposited long period fiber grating for continuous refractive index sensor applications

Abstract: We present a carbon-nanotube-deposited long period fiber grating for refractive index sensing applications in liquid. Carbon nanotubes are deposited around the surface of a long period fiber grating to form the refractive index sensing element. The sensing mechanism relies mainly on the high refractive index properties of the carbon nanotube thin film, which enhances the cladding mode of the long period fiber grating in order to have a significant interaction between the propagating light and the target medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…12 shows a nonlinear response of the resonance band intensity with increasing RI values. These observations are consistent with previously reported studies with GO [18] and carbon nanomaterial [19] based fibre optic RI sensors. Calculations based on the figure showed that in the lower region of RI values (from 1.33 to 1.38), an approximate sensitivity of 17dB/RIU has been achieved, compared to the higher RI region (values from 1.4 to 1.45), where an approximate sensitivity of 55 dB/RIU was achieved.…”
Section: B Temperature Responsesupporting
confidence: 94%
“…12 shows a nonlinear response of the resonance band intensity with increasing RI values. These observations are consistent with previously reported studies with GO [18] and carbon nanomaterial [19] based fibre optic RI sensors. Calculations based on the figure showed that in the lower region of RI values (from 1.33 to 1.38), an approximate sensitivity of 17dB/RIU has been achieved, compared to the higher RI region (values from 1.4 to 1.45), where an approximate sensitivity of 55 dB/RIU was achieved.…”
Section: B Temperature Responsesupporting
confidence: 94%
“…The coupling coefficient between optical modes is a function of the SRI. The increasing SRI reduces the overlap integral between core and cladding modes, hence the decreasing of resonant intensity (Erdogan, 1997;Tan et al, 2014). When the SRI approaches that of cladding, the core mode will be coupled to the broadband radiation mode with no distinct attenuation bands.…”
Section: Characteristics Of Sensitivity In Refractive Indexmentioning
confidence: 99%
“…Accurate multi-parameter detection and mapping with integrated chips show promise for precision applications such as manned spacecraft, intensive care units, and gas reaction chambers. [5,6] The gas refractive index (RI) is a comprehensive parameter [7][8][9] that can be correlated with other essential parameters noted above, under certain conditions. Therefore, monitoring the RI is an effective way to achieve multi-parameter detection.…”
Section: Introductionmentioning
confidence: 99%